English in public primary schools in Colombia: Achievements and challenges brought about by national language education policies - Correa, Doris; González, Adriana (Education Policy Analysis Archives, 2016)
In an effort to become more competitive in the global market, Colombia, as many other Latin American countries, has declared English the dominant foreign language to be taught in schools and universities across the country. To support this measure, in the last 16 years, the government, through its National Ministry of Education, has launched a series of programs such as National Program of Bilingualism 2004-2019; the Program for Strengthening the Development of Competences in Foreign Languages; The National English Program: Colombia Very Well 2015-2025; and most recently, Bilingual Colombia 2014-2018. Results from studies conducted by local researchers across the country suggest that the regulation has posed a series of challenges for public primary school teachers, which these programs have not been able to address. These challenges can be divided into two categories: professional and work related. The purpose of this article is twofold: First, the article intends to provide a critical overview of the four programs that the Colombian government has launched since 2004. Second, the article aims to present some conclusions and recommendations for language policy design and implementation in Colombia.